Kelayakan Finansial Dan Nilai Tambah Produk Olahan Ikan (Amplang Kuku Macan Al-Izza) - Rahmawati, Meylin; Pratiwi, Sulistya Rini; Kartini, Kartini; Irna, Rizky Agusriyanti; Putri, Ferica C; Nainggolan, Yohanna Thresia (AL-MIKRAJ Jurnal Studi Islam dan Humaniora, 2023)
This research aims to address the issues faced by Al-Izza MSMEs, particularly regarding their tiger nail snack product, such as limited capital, availability of raw materials, and competitiveness against similar products. The objectives of this study are: 1) to analyze the financial feasibility of the tiger nail snack product, and 2) to analyze the value-added of the tiger nail snack product. The data obtained are quantitative and processed and presented in tabular form. The sample selection method used purposive sampling. The total monthly expenses incurred by the business owner amount to Rp. 4,371,028. The monthly revenue is Rp. 8,640,000, resulting in a monthly profit of Rp. 4,268,972, and the R/C ratio is greater than one, specifically 1.97, indicating that the business is viable. The Break Even Point (BEP) price is Rp. 6,071 < Rp. 12,000, BEP production is 28 < 720 packages, and BEP revenue is Rp. 330,939 < 8,640,000. Based on these BEP calculations, it can be concluded that the business is feasible. Meanwhile, the value-added of milkfish is Rp. 276,125 per kg, indicating a high value-added ratio of 76.70% > 40%. Considering the high value-added ratio of the milkfish raw material, the business is highly feasible. Therefore, it is advisable for the business owner to increase the production capacity of the tiger nail snack product to achieve greater profits.